Play Therapy : A Tool For Counseling Children. - See, Ching Mey (2006)
Play Therapy is based upon the fact that play is the child's natural mediurn of self expression. lt is an opportunity which is given to the child to "play out" his thoughts, feelings and problems, just as in adult counseling where an individual "talks out".